Chemical composition and degradation characteristics of foliage of some African multipurpose trees - El Hassan, S.M.; Lahlou-Kassi, A.; Newbold, C.J.; Wallace, R.J. (Elsevier, 2000)
Samples of foliage from multipurpose leguminous trees (MPT) which had been selected as potential feed supplements for ruminants were examined for their chemical composition and in situ degradation characteristics, and were compared with alfalfa (Medicago sativa) hay and teff (Eragrostis abyssinica) straw. Organic matter (OM), acid detergent fibre (ADF), neutral detergent fibre (NDF), nitrogen, neutral detergent nitrogen, acid detergent lignin (ADL), soluble phenolics, NDF-bound proanthocyanidins and in vitro digestibility were determined in Acacia angustissima, Chamaecytisus palmensis (Tagasaste), Leucaena leucocephala, two cultivars of Sesbania sesban and Vernonia amygdalina (bitter leaf). The MPT all had a nutrient content, particularly in terms of N (up to 39.5 g available N per kg dry matter (DM) similar to alfalfa hay, which would be suitable for supplementing teff straw, which had a high fibre, but low N(4.0 g available N per kg DM) content. In situ nylon bag digestion and in vitro gas production analyses were carried out to assess microbial degradation characteristics. The MPT were highly degradable in situ, however gas production in vitro decreased at the MPT: teff straw ratio increased in A. angustissima, indicating that antimicrobial components were present in this species. None of the chemical estimations were correlated with antimicrobial properties. It is concluded that some of the MPT tested may prove to be useful dietary supplements for ruminants receiving poor quality forages like teff straw, as has been found in other studies. However, chemical analysis alone will be of limited value in predicting the nutritive value of a new MPT which contains antimicrobial components or material toxic to the animal itself.